The effective adsorption of tetracycline onto zirconia nanoparticles synthesized by novel microbial green technology. (1st May 2020) - Debnath, Banhishikha; Majumdar, Moumita; Bhowmik, Mahashweta; Bhowmik, Kartick Lal; Debnath, Animesh; Roy, Dijendra Nath
Abstract: Pseudomonas aeruginosa bacteria have been used in this study for zirconia nanoparticles synthesis through green technology for adsorption driven bioremediation of tetracycline from wastewater. The characterization of synthesized nano zirconia has been performed by employing dynamic light scattering, field emission-transmission electron microscopy, energy dispersive X-ray, X-ray diffraction, fourier transform infrared spectroscopy, and point of zero charge analysis. The zirconia nanoparticles have shown average particle size ~15 nm, monoclinic and tetragonal crystal structure with 6.41 nm of crystallite size, the presence of elemental zirconium and oxygen, and the occurrence of functional groups like O–Zr–OH, Zr–O–Zr and Zr–O bonds. The zirconia nanoparticles mediated adsorption of tetracycline has been found to be effective at solution pH 6.0 and in a very less contact time 15 min. Strong electrostatic interaction between zwitterionic form of tetracycline and protonated surface of zirconia nanoparticles is the governing adsorption mechanism in this study. The kinetic study has been performed on the basis of the tetracycline adsorption process revealing that the adsorption phenomenon follows pseudo-second order kinetic, further suggesting chemisorption of tetracycline over zirconia nanoparticles. The Langmuir isotherm model has been found to be the best fitted model among the all isotherm models indicating the involvement of monolayer uptake of tetracycline on the surface of zirconia nanoparticles. Moreover, the maximum tetracycline adsorption capacity of zirconia nanoparticles calculated by the Langmuir isotherm model is close to 526.32 mg/g. This finding is quite reasonable to accept that zirconia nanoparticle may be used as an alternative adsorbent to mitigate the tetracycline contamination in wastewater. Highlights: Green synthesis of zirconia nanoparticles by microbial cell free culture supernatant. The zirconia nanoparticles show an average size ~15 nm. Monolayer uptake of tetracycline on the surface of zirconia nanoparticles through chemisorption process. Strong electrostatic interaction involved between tetracycline and zirconia nanoparticles.